SAS code to analyze a complete dialelic and heterosis. An environment - Pérez López, Delfina de Jesús; Saavedra Guevara, Claudia; Rubí Arriaga, Martín; Franco Martínez, J. Ramón Pascual; Gutiérrez Rodríguez, Francisco; González Huerta, Andrés (Revista Mexicana de Ciencias Agrícolas, 2020)
The development of statistical analysis system (SAS) programs and their validation with freely available software is essential when there are no financial resources to acquire the license of an appropriate statistical package. In this study a code for SAS is presented and its validation is performed with the program proposed by Zhang and Kang (1997), modified by Saavedra (2019). The code generates an analysis of variance with partition of the effects of treatments on parents (P), direct crosses (CD), reciprocal crosses (CR), P vs crosses, and CD vs CR. In addition to generating the comparison of treatment means with the Tukey test, the genetic effects for parents or for their crosses are estimated (Gi, Sij, Rij, Mi); as well as, those of heterosis with the average of both parents or with the best of them. Since both codes only coincide in the calculation of the previously indicated genetic effects, their simultaneous application is suggested to carry out a complete analysis of Griffing’s method 1 (1956a, b). The code that has been proposed will be especially useful for plant breeders and geneticists and especially for undergraduate and graduate level biological and agricultural science students with little training in the programming language at SAS.
Keywords: Griffing method 1; model 1; randomized complete blocks; Tukey test